Remley, Zita Donegan (audio interview #3 of 6) - Donegan Remley, Zita (11/4/1904 - 8/1/1985); Fischer, Jan, interviewer
INTERVIEW DESCRIPTION - This is the third of six interviews with Zita Remley conducted over the course of two years and is part of a longer life history project that was initiated for a women's oral history course in the summer of 1976. 7/16/1976